The likelihood of developing hypoglycaemic states may be an individual risk factor in elite canoeists - Makarova, G. A.; Pogrebnoy, A. I.; Chernukha, S. M.; Karpov, A. A. (Theory and Practice of Physical Culture, 2025)
Objective of the study aims to establish the significance of possible hypoglycemia in a complex of risk factors that have a negative impact on the functional state of the body of highly qualified athletes involved in canoeing and kayaking.